The role of international regimes and courts in clarifying prevention of harm in freshwater and marine environmental protection - Ruby Moynihan; Bjørn-Oliver Magsig (International Environmental Agreements: Politics, Law and Economics, 2020)

Efficient production of fatty acid methyl esters by a wastewater-isolated microalgae-yeast co-culture - Jessica K. Suastes-Rivas; Raúl Hernández-Altamirano; Violeta Y. Mena-Cervantes; Ruby Valdez-Ojeda; Tanit Toledano-Thompson; Luis R. Tovar-Gálvez; Silvia López-Adrián; Isaac Chairez (Environmental Science and Pollution Research, 2020)

Transcatheter Mitral Valve Replacement: State of the Art - Dylan Goode; Ruby Dhaliwal; Hadi Mohammadi (Cardiovascular Engineering and Technology, 2020)

Males and females exhibit similar muscle glycogen recovery with varied recovery food sources - Shannon Flynn; Alejandro Rosales; Walter Hailes; Brent Ruby (European Journal of Applied Physiology, 2020)
Purpose Research has elucidated the impact of post-exercise carbohydrate nutrition and environmental conditions on muscle glycogen re-synthesis. However, research has minimally considered the implications of glycogen recovery in females and has mostly focused on commercial sport nutrition products. The purpose of this study was to determine the effects of varied mixed macronutrient feedings on glycogen recovery and subsequent exercise performance in both sexes. Methods Males ( n = 8) and females ( n = 8) participated in a crossover study. Subjects completed a 90-min cycling glycogen depletion trial, then rested for 4 h. Two carbohydrate feedings (1.6 g kg −1 ) of either sport supplements or potato-based products were delivered at 0 and 2 h post-exercise. Muscle biopsies (glycogen) and blood samples (glucose, insulin) were collected during the recovery. Afterwards, subjects completed a 20 km cycling time trial. Results There was no difference between sexes or trials for glycogen recovery rates (male: 7.9 ± 2.7, female: 8.2 ± 2.7, potato-based: 8.0 ± 2.5, sport supplement: 8.1 ± 3.1 mM kg wet wt −1 h −1 , p > 0.05). Time trial performance was not different between diets (38.3 ± 4.4 and 37.8 ± 3.9 min for potato and sport supplement, respectively, p > 0.05). Conclusions These results indicate that food items, such as potato-based products, can be as effective as commercially marketed sports supplements when developing glycogen recovery oriented menus and that absolute carbohydrate dose feedings (g kg −1 ) can be effectively applied to both males and females.

Marine latitudinal diversity gradients, niche conservatism and out of the tropics and Arctic: Climatic sensitivity of small organisms - Wing‐Tung Ruby Chiu; Moriaki Yasuhara; Thomas M. Cronin; Gene Hunt; Laura Gemery; Chih‐Lin Wei (Journal of Biogeography, 2020)
Aim The latitudinal diversity gradient (LDG) is a consequence of evolutionary and ecological mechanisms acting over long history, and thus is best investigated with organisms that have rich fossil records. However, combined neontological‐palaeontological investigations are mostly limited to large, shelled invertebrates, which keeps our mechanistic understanding of LDGs in its infancy. This paper aims to describe the modern meiobenthic ostracod LDG and to explore the possible controlling factors and the evolutionary mechanisms of this large‐scale biodiversity pattern. Location Present‐day Western North Atlantic. Taxon Ostracoda. Methods We compiled ostracod census data from shallow‐marine environments of the western North Atlantic Ocean. Using these data, we documented the marine LDG with multiple metrics of alpha, beta (nestedness and turnover) and gamma diversity, and we tested whether macroecological patterns could be governed by different environmental factors, including temperature, salinity, dissolved oxygen, pH and primary productivity. We also explored the geologic age distribution of ostracod genera to investigate the evolutionary mechanisms underpinning the LDG. Results Our results show that temperature and climatic niche conservatism are important in setting LDGs of these small, poorly dispersing organisms. We also found evidence for some dispersal‐driven spatial dynamics in the ostracod LDG. Compared to patterns observed in marine bivalves, however, dispersal dynamics were weaker and they were bi‐directional, rather than following the ‘out‐of‐the‐tropics’ model. Main conclusions Our detailed analyses revealed that meiobenthic organisms, which comprise two‐thirds of marine diversity, do not always follow the same rules as larger, better‐studied organisms. Our findings suggest that the understudied majority of biodiversity may be more sensitive to climate than well‐studied, large organisms. This implies that the impacts of ongoing Anthropocene climatic change on marine ecosystems may be much more serious than presently thought.

A substantial role of soil erosion in the land carbon sink and its future changes - Zeli Tan; L. Ruby Leung; Hong‐Yi Li; Teklu Tesfa; Qing Zhu; Maoyi Huang (Global Change Biology, 2020)
Realistic representation of land carbon sink in climate models is vital for predicting carbon climate feedbacks in a changing world. Although soil erosion that removes land organic carbon has increased substantially since the onset of agriculture, it is rarely included in the current generation of climate models. Using an Earth system model (ESM) with soil erosion represented, we estimated that on average soil erosion displaces 5% of newly fixed land organic carbon downslope annually in the continental United States. In the lower Mississippi river basin and the Cascades, the fraction can be as large as 40%. About 12% of the eroded organic carbon is eventually exported to inland waters, which is equal to 14% of the simulated net carbon gain by terrestrial ecosystems. By comparing the eroded organic carbon export to rivers with the particulate organic carbon export to oceans, we demonstrated that a large fraction of the carbon export to rivers could have been mineralized in inland waters. Importantly, with a direct comparison of eroded and exported soil organic carbon and land net carbon uptake, we found that ESMs that ignore soil erosion likely offset the erosional carbon loss by increasing heterotrophic respiration implicitly. But as soil erosion and heterotrophic respiration respond differently to a warming climate, this unrealistic compensation would lead to biased predictions of future land carbon sink.

Structural changes and variability of the ITCZ induced by radiation–cloud–convection–circulation interactions: inferences from the Goddard Multi-scale Modeling Framework (GMMF) experiments - William K. M. Lau; Kyu-Myong Kim; Jiun-Dar Chern; W. K. Tao; L. Ruby Leung (Climate Dynamics, 2020)
In this paper, we have investigated the impact of radiation–cloud–convection–circulation interaction (RC3I) on structural changes and variability of the Inter-tropical Convergence Zone (ITCZ) using the Goddard Multi-scale Modeling Framework, where cloud processes are super-parameterized, i.e., explicitly resolved with 2-D cloud resolving models embedded in each coarse grid of the host Goddard Earth Observing System-Version 5 global climate model. Experiments have been conducted under prescribed sea surface temperature conditions for 10 years (2007–2016), with and without cloud radiation feedback in the atmosphere, respectively. Diagnostic analyses separately for January and July show that RC3I leads to an enhanced and expanded Hadley Circulation characterized by (1) a quasi-uniform warming and moistening of the tropical atmosphere and a sharpening of the ITCZ with enhanced deep convection, more intense precipitation and higher clouds, (2) extended drying of the tropical marginal convective zones, and extratropical mid- to lower troposphere, and (3) a cooling of the polar regions, with increased baroclinicity and midlatitude storm track activities. Computations based on the zonal mean thermodynamic energy balance equation show that the radiative warming and cooling are strongly balanced by local adiabatic processes associated with changes in large-scale vertical motions, as well as horizontal atmospheric heat transport. In the tropics, enhanced short-wave absorption and longwave water vapor greenhouse effects by high clouds play key roles in providing strong positive feedback to the tropospheric warming. In the extratropics, increased atmospheric heat transport associated with changes in the Hadley circulation is balanced by strong longwave cooling above, and warming below due to increased high clouds. We also find a strong positive correlation between daily and pentad heavy rain in the ITCZ core, and expansion of the drier zones coupled to a contraction of the highly convective zones in the ITCZ, indicating a strong tendency RC3I-induced convective aggregation in tropical clouds i.e., wet-regions-get-wetter and contracted, and dry-areas-get-drier and expanded.